Peran Sistem Akuntansi Instansi Berbasis Akrual dalam Meningkatkan Kualitas Laporan Keuangan - Najati, Ida; Pituringsih, Endar; Animah, Animah (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
The study objectives are to empirically examine the influence of usage of SAIBA as relationship between accrual accounting implementation and quality of Ministry/Board financial accounting report (LKKL). The research population are 464 SAIBA operators of KPPN Makassar I and II stakeholders. Samples quantity which determined by Slovin technique and cluster sampling are 82 respondents, consist of 33 respondents on KPPN Makassar I and 49 respondents on KPPN Makassar II. Data analysis tool used is PLS with second order confirmatory factor analysis. The finding shows that accrual accounting implementation has a significant effect on usage of SAIBA and the usage of SAIBA has a significant effect to quality of Ministry/Board financial accounting report (LKKL). The other finding indicated that accrual accounting implementation has significant effect on quality of Ministry/Board financial accounting report (LKKL). The maximum implementor use SAIBA in the preparation of accrual-based financial accounting report, the more it will improve the quality of Ministry/Board financial accounting report (LKKL).
Keywords: Kementerian, akrual, SAIBA